Commentary to the paper V.D. tran, D.t. Pham, t.t.n. Cao, m. Bahlol, r.S. Dewey, m.H. Le, V.a. nguyen. Perspectives on CoVID-19 prevention and treatment using herbal medicine in Vietnam: a cross-sectional study (ann Ig. 2022 Sept-oct; 34(5): 515-531. doi - Papini, F.; Privitera, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
.